Cost‐Effective and Robust Multispectral Light‐Emitting Diode Device for the Readout of Plasmonic Microarray Sensors. Issue 2 (8th December 2022) - Kastner, Stephan; Urban, Matthias; Dietel, Anne-Kathrin; Csáki, Andrea; Fritzsche, Wolfgang
Abstract : Localized surface plasmon resonance (LSPR) is a phenomenon known for more than 100 years, which arises from the interaction of light with metallic nanoparticles. In recent years, the field of LSPR sensing has become increasingly important in bioanalytics. Herein, a simple and robust device setup to perform time‐resolved LSPR measurements with inexpensive array sensor chips is presented. For this purpose, gold nanoparticles are spotted onto glass substrates under different conditions (droplet size/number, temperature, and humidity) to achieve an optimal signal‐to‐noise ratio. To verify the setup and the spotted sensor chips, bulk sensitivity measurements with solutions of varying refractive index and surface sensitivity measurements with layer‐by‐layer (LbL) deposition are performed. It is shown that slower drying minimizes the edge effects of ring‐like deposits (coffee ring effect) and that the spots with higher particle densities are more suitable for sensor applications. In general, the use of six light‐emitting diode (LEDs) enables a simple centroid calculation as well as an evaluation via individual LED intensities. The presented cost‐effective system allows parallel reading of more than 100 spots in a label‐free platform, and together with the optimized low‐cost sensors, it provides an interesting alternative for the development of future on‐site diagnostics. Abstract : An innovative imaging spectroscopic light‐emitting diode (LED)‐based readout of plasmonic nanoparticle sensors for the label‐free detection of molecular interactions is introduced, combined with spotted nanoparticle microarray sensors which are optimized by adjusting the spotting conditions. Both instrument and sensors are robust and cost‐efficient to manufacture and provide time‐resolved sensorgrams of multiplex localized surface plasmon resonance assays.